Oxidative Post-translational Protein Modifications upon Ischemia/Reperfusion Injury - Aleksandra Binek; Celia Castans; Inmaculada Jorge; Navratan Bagwan; José Manuel Rodríguez; Rodrigo Fernández-Jiménez; Carlos Galán-Arriola; Eduardo Oliver; Mónica Gómez; Agustín Clemente-Moragón; Borja Ibanez; Emilio Camafeita; et al. (MDPI AG, 2024)
While reperfusion, or restoration of coronary blood flow in acute myocardial infarction, is a requisite for myocardial salvage, it can paradoxically induce a specific damage known as ischemia/reperfusion (I/R) injury. Our understanding of the precise pathophysiological molecular alterations leading to I/R remains limited. In this study, we conducted a comprehensive and unbiased time-course analysis of post-translational modifications (PTMs) in the post-reperfused myocardium of two different animal models (pig and mouse) and evaluated the effect of two different cardioprotective therapies (ischemic preconditioning and neutrophil depletion). In pigs, a first wave of irreversible oxidative damage was observed at the earliest reperfusion time (20 min), impacting proteins essential for cardiac contraction. A second wave, characterized by irreversible oxidation on different residues and reversible Cys oxidation, occurred at late stages (6-12 h), affecting mitochondrial, sarcomere, and inflammation-related proteins. Ischemic preconditioning mitigated the I/R damage caused by the late oxidative wave. In the mouse model, the two-phase pattern of oxidative damage was replicated, and neutrophil depletion mitigated the late wave of I/R-related damage by preventing both Cys reversible oxidation and irreversible oxidation. Altogether, these data identify protein PTMs occurring late after reperfusion as an actionable therapeutic target to reduce the impact of I/R injury.